Immersive Virtual Reality Feedback in a Brain Computer Interface for Upper Limb Rehabilitation - Achanccaray D. (2019)
Visual feedback in a brain computer interface (BCI) influences significantly in its performance; but when this BCI will be applied in a rehabilitation therapy for post stroke patients, it will be a determining factor to enhance the neuroplasticity process. Many studies have demonstrated the efficiency of virtual reality (VR) in a BCI, motor cortex increases its activation levels due to be an immersive environment for the subject; specifically, a BCI based on motor imagery (MI) with VR feedback has positive effects in patients. This work proposes to apply a BCI with VR to support an upper limb rehabilitation therapy for post stroke patients, but it has been tested with eighteen healthy subjects, they performed MI tasks of flexion and extension of their arms, then they could see a virtual arm in 3D performing the same requested movement. Comparison of power spectral density (PSD) estimation is done during MI tasks in training and online test sessions, and feedback in online test sessions; and it is possible to observe the brain activity in alpha and beta bands remained during online sessions, topographic map shows activated premotor and motor cortex areas, it is significant evidence for the application of this system to motor disable patients.